2019
DOI: 10.1029/2018jd029338
|View full text |Cite
|
Sign up to set email alerts
|

Aerosolization of Crude Oil‐Dispersant Slicks Due to Bubble Bursting

Abstract: Bubble bursting is a primary source of marine aerosols, yet little is known about particle emissions due to the bubble bursting in slicks containing oil‐dispersant mixtures. In this study, bubbles with mode sizes of 86 μm (denoted as small), 178 μm (medium), and 595 μm (large) are injected into a seawater column covered by slicks of crude oil, pure dispersant, and dispersant premixed with oil at a ratio of 1:25. The aerosol size distributions are monitored in the 0.5‐ to 20‐μm and 10‐ to 380‐nm ranges both in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 83 publications
1
25
0
Order By: Relevance
“…Our findings demonstrate a distinct transport mechanism related to dynamics of the bubble bursting jetting at a compound interface. Although previous studies have reported evidence of oily aerosol generation by bubble bursting at a contaminated surface 44,45 , only film droplets are considered to be responsible for the dispersion of the insoluble surface contaminants, including bacteria and aliphatic-rich hydrophobic organic species in the surface microlayer 15,19 , while the jet droplets are believed to only contribute to the transport of more soluble organic species from the underlying seawater 15,46,47 . In this study, we highlight the 12) and ( 13), and the dashed lines represent the scaling laws of Eqs.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings demonstrate a distinct transport mechanism related to dynamics of the bubble bursting jetting at a compound interface. Although previous studies have reported evidence of oily aerosol generation by bubble bursting at a contaminated surface 44,45 , only film droplets are considered to be responsible for the dispersion of the insoluble surface contaminants, including bacteria and aliphatic-rich hydrophobic organic species in the surface microlayer 15,19 , while the jet droplets are believed to only contribute to the transport of more soluble organic species from the underlying seawater 15,46,47 . In this study, we highlight the 12) and ( 13), and the dashed lines represent the scaling laws of Eqs.…”
Section: Discussionmentioning
confidence: 99%
“…(1954), Blanchard & Woodcock (1957), Veron (2015) and Sampath et al. (2019); disease and pandemic transmission, e.g. Bourouiba (2021)) and in more ‘indulging’ applications (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…While the size distributions of marine aerosols have received considerable attention (Veron, 2015), very limited information exists about the process of aerosolization of oil slicks. However, a series of experiments investigated the effect of dispersants on the aerosolization of oil slicks by breaking waves (Afshar-Mohajer et al, 2018), and subsequently, the effect of bubble bursting at an oil-water interface (Sampath et al, 2019;Afshar-Mohajer et al, 2020).…”
Section: Aerosolization Of Oilmentioning
confidence: 99%
“…In an attempt to identify and characterize the mechanisms affecting the generation of nanodroplets, subsequent studies focused on generation of airborne droplets by bursting of rising gas bubbles at the liquid-air interface (Sampath et al, 2019). Bubbles with different size ranges were injected into a seawater column covered by slicks of crude oil, pure dispersant, and a DOR 1:25 dispersant-oil mixture; the sensors mentioned above were used to measure nano-and micro-aerosol size distributions in both clean and ambient air environments.…”
Section: Aerosolization Of Oilmentioning
confidence: 99%